(untitled) (Research, Society and Development, 2022)
Objective: to identify the evidence available in the Latin American literature on the perception of nursing care by hospitalized patients. Methodology: Integrative Literature Review, starting from the guiding question: "What is the patient’s perception of nursing care when admitted to a hospital unit?". Searches were carried out in scientifically recognized libraries and databases, namely: Scientific Eletronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Science (LILACS) and Virtual Health Library (BVS), making crossings between descriptors Patient Care, Nurse-Patient Relations and Patient Satisfaction, present in the site Descriptors in Health Science (DeCS). Results: 14 articles were selected for final analysis, with predominant level of evidence IV. It was possible to observe that nurses are present during the entire hospitalization process of patients, in its various cycles, with results that went through the period of delivery and puerperium, surgical patients, oncology patients, dialysis patients and in children’s hospitalization units. The discussion was organized into two main categories: "Patient satisfaction assessment tools and main Nursing care provided in the hospital environment" and "The Educational domain of the Nurse: obstacles to satisfaction". Conclusion: Although there are still some gaps during the process of care by nurses, their scientific/technical expertise was evident, which provided safety during the care provided, and their interpersonal skills as caregivers, providing a welcoming environment that took into account physiological, emotional and cultural aspects of patients, ensuring the creation of trust and bond.